Scoping review to identify strategies and interventions improving interprofessional collaboration and integration in primary care - Roy Remmen; Kris Van den Broeck; Peter Pype; Peter Van Bogaert; Muhammed Mustafa Sirimsi; Hans De Loof; Kristel De Vliegher (BMJ Open)
Objective To identify strategies and interventions used to improve interprofessional collaboration and integration (IPCI) in primary care.Design Scoping reviewData sources Specific Medical Subject Headings terms were used, and a search strategy was developed for PubMed and afterwards adapted to Medline, Eric and Web of Science.Study selection In the first stage of the selection, two researchers screened the article abstracts to select eligible papers. When decisions conflicted, three other researchers joined the decision-making process. The same strategy was used with full-text screening. Articles were included if they: (1) were in English, (2) described an intervention to improve IPCI in primary care involving at least two different healthcare disciplines, (3) originated from a high-income country, (4) were peer-reviewed and (5) were published between 2001 and 2020.Data extraction and synthesis From each paper, eligible data were extracted, and the selected papers were analysed inductively. Studying the main focus of the papers, researchers searched for common patterns in answering the research question and exposing research gaps. The identified themes were discussed and adjusted until a consensus was reached among all authors.Results The literature search yielded a total of 1816 papers. After removing duplicates, screening titles and abstracts, and performing full-text readings, 34 papers were incorporated in this scoping review. The identified strategies and interventions were inductively categorised under five main themes: (1) Acceptance and team readiness towards collaboration, (2) acting as a team and not as an individual; (3) communication strategies and shared decision making, (4) coordination in primary care and (5) integration of caregivers and their skills and competences.Conclusions We identified a mix of strategies and interventions that can function as ‘building blocks’, for the development of a generic intervention to improve collaboration in different types of primary care settings and organisations.